PENGARUH PENGGUNAAN MEDIA ANIMASI DAN KESIAPAN BELAJAR TERHADAP MINAT BELAJAR IPA SISWA KELAS V - Sutria, Dewi; Murbojono, Rahmat; Rusdi, Muhammad (Program Magister Teknologi Pendidikan Universitas Jambi, 2012)
This research aims to know the differences of interest in learning through the application of media animation and conventional learning in IPA learning. Sample of this research is determined by quasi experimental design and take two classes samples, namely experiment class use media animation and control class use the conventional learning models. The research instrument is used: 1) the learning design by using the media animation and conventional learning design, 2) learning readiness questionnaire, 3) evaluation in the form interest questionnaire. Analysis of the data used is analysis of covariant (ANCOVA). The result of this research showed that: 1) interests in learning IPA, the student who have a high readiness, higher when compared with the interest in learning IPA that student have a low readiness. 2) Interest in learning IPA students are taught by media animation is no different with interest in learning IPA that student is taught by conventional. The result of this research when analyzed by ANCOVA can be concluded that: 1) there is a linear relationship between learning readiness and interest in learning IPA, 2) there is no difference between interest in learning IPA in experiment class with in learning IPA in control class. Kata kunci: media animation, learning readiness, interest in learning